Contribution of water chemistry and fish condition to otolith chemistry: comparisons across salinity environments. Issue 6 (June 2015) - Izzo, C.; Doubleday, Z. A.; Schultz, A. G.; Woodcock, S. H.; Gillanders, B. M.
<x xml:space="preserve">Abstract</x> This study quantified the per cent contribution of water chemistry to otolith chemistry using enriched stable isotopes of strontium (86Sr) and barium (137Ba). Euryhaline barramundi Lates calcarifer, were reared in marine (salinity 40), estuarine (salinity 20) and freshwater (salinity 0) under different temperature treatments. To calculate the contribution of water to Sr and Ba in otoliths, enriched isotopes in the tank water and otoliths were quantified and fitted to isotope mixing models. Fulton's K and RNA:DNA were also measured to explore the influence of fish condition on sources of element uptake. Water was the predominant source of otolith Sr (between 65 and 99%) and Ba (between 64 and 89%) in all treatments, but contributions varied with temperature (for Ba), or interactively with temperature and salinity (for Sr). Fish condition indices were affected independently by the experimental rearing conditions, as RNA:DNA differed significantly among salinity treatments and Fulton's K was significantly different between temperature treatments. Regression analyses did not detect relations between fish condition and per cent contribution values. General linear models indicated that contributions from water chemistry to otolith chemistry were primarily influenced by temperature and secondly by fish condition, with a relatively minor influence of salinity. These results further the understanding of factors that affect otolith element uptake, highlighting the necessity to consider the influence of environment and fish condition when interpreting otolith element data to reconstruct the environmental histories of fish.